A new family within the holothuroid order Dactylochirotida with description of a new species from South Africa and comments on the dendrochirotid genus Neoamphicyclus Hickman, 1962 and the molpadid genus Cherbonniera Sibuet, 1974 (Echinodermata) - Thandar, Ahmed; Arumugam, Preyan (Zootaxa, 2011)
A new species of Cucumella, C. triperforata, with simple, digitate tentacles is described from deep waters off the east coast of South Africa. Since C. triplex, the type species of this genus, also has simple, digitate tentacles, the genus Cucumella together with its type species is removed from the Dendrochirotida and re-assigned to a new family, Cucumellidae, within the Dactylochirotida. The remaining species of Cucumella, with the exception of C. decaryi Cherbonnier (= Neostichopus grammatus (H.L. Clark, 1923)) are assigned to Neoamphicyclus Hickman, 1962 within the dendrochirotid subfamily Thyonidiinae. The ossicles of the new species bear a striking resemblance to those of the molpadid Cherbonniera utriculus Sibuet, but ordinal differences readily separate the taxa.